2015
DOI: 10.1097/brs.0000000000000689
|View full text |Cite
|
Sign up to set email alerts
|

Discectomy-Related Information on the Internet

Abstract: The overall quality of information regarding discectomy remains poor and variable despite an exponential increase in the number of users and Web sites, with a slight trend toward improvement, only 20% to 30% are of good quality, compared with that 10 years ago (<10%). Presence of Health on the Net code is a very reliable marker for health information quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 8 publications
3
30
0
Order By: Relevance
“…The finding of higher DISCERN scores among institutional sites is consistent with recently published data. 33 The high Cronbach's alpha score supports the use of the DISCERN criteria to guide the development and evaluation of future Internet content in this topic area.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The finding of higher DISCERN scores among institutional sites is consistent with recently published data. 33 The high Cronbach's alpha score supports the use of the DISCERN criteria to guide the development and evaluation of future Internet content in this topic area.…”
Section: Discussionmentioning
confidence: 88%
“…The median score of 51 is significantly higher than a mean of 37.9 found in a 2015 study of online information on vertebral discectomy, an orthopedic procedure. 33 Component scores were high for aims and relevance. Areas of significant deficits include use and dates of citations, describing impact of treatment on QOL, describing the risks of no treatment, and content which supports shared decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to capturing of these data on a single day, it gives only a snapshot of the information accessible at a specific time. The internet is a common source of information through which individuals can constantly remove media from or upload it on open source forums such as YouTube leading to flow of quality and quantity and continual ebb 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…18 In internet-based studies of spinal diseases, the authors observed that the clinical information available on the Internet was of generally poor quality. 9,[19][20][21][22][23][24][25][26][27] To our knowledge, no published studies have evaluated internet resources on the spinal disease kyphosis. Therefore, this study aimed to assess the content, quality, and readability of information available online about kyphosis.…”
Section: Introductionmentioning
confidence: 99%